PENERAPAN ASAS-ASAS BUDAYA ORGANISASI UNTUK MENCEGAH TINDAKAN FRAUD PADA KARYAWAN PT. BANK RIAU KEPRI SYARIAH CABANG PEKANBARU - Erfiyanti, Fina; Andri, Seno; Zulkarnaini, Zulkarnaini (Jurnal Progress Administrasi Publik, 2023)
Fraud cases in financial institutions in Indonesia have increased. Currently, the banking sector is experiencing intense competition and facing internal problems, including fraud. Banks are institutions that depend on public trust in their operations because banks are considered agents of trust. Therefore, building public trust is very important for banks so that people are interested in using banking services. In the context of PT. Bank Riau Kepri Syariah, they also integrate organizational cultural values as moral guidance in behavior, actions and decision making. These values become a reference for all PT members. Bank Riau Kepri Syariah in assessing whether the actions taken are good or bad, right or wrong. The aim of this research is to analyze how the Principles of Organizational Culture are implemented in preventing fraud among PT employees. Bank Riau Kepri Syariah Pekanbaru Branch uses descriptive qualitative methods with an ethnographic approach which aims to explore behavior that occurs naturally in a culture or a certain social group to understand a particular culture from the perspective of the perpetrator. Data collection techniques in this research are based on the results of interviews, observation and documentation. The results of this research indicate that the application of PT's Cultural Values. Bank Riau Kepri Syariah Pekanbaru Branch has been well organized.   Keywords: Organizational Culture; Fraud; Bank.